Digital Learning Tools in Arabic Second Language Acquisition: A Case Study / أدوات التعلم الرقمي في اكتساب اللغة العربية كلغة ثانية: دراسة حالة - Farih Muzaky; Muhammad Qadhaf (IJAS: International Journal of Arabic Studies, 2025)
The rapid advancement of digital learning tools has significantly influenced the acquisition of Arabic as a second language (ASLA). This study examines the impact of mobile applications and online platforms on ASLA learners, focusing on their effectiveness in enhancing language skills, including speaking, reading, writing, and listening. Using a mixed-methods approach, this research incorporates quantitative data from surveys and qualitative insights from interviews and classroom observations. The findings indicate that digital learning tools contribute positively to ASLA acquisition, particularly through gamification, AI-based tutoring, and interactive platforms. However, challenges such as technical barriers, limited feedback mechanisms, and the need for contextualized cultural integration persist. The study highlights the importance of combining digital learning tools with traditional teaching methods to optimize language learning outcomes. Future research is recommended to explore the long-term effects of digital learning tools on Arabic language acquisition and develop more adaptive and culturally relevant educational technologies.